El trabajo infantil atenta contra nuestros derechos - Hoyos Lescano, Auner Humberto (2019)
The present Professional Suficiencia's work, it is developing my learning, named session The child labor attentive our rights, directed to the Primary students of Educación's fourth degree, Institución Educativa Santa María of hope N 808222 at Trujillo's City._x000D_ The work of professional sufficiency, he consists of a learning session's design, in the Personal Social area, in the competition Live Together and he participates democratically in the search of the public interest, that he has for purpose, to develop the demonstrative class, deploying a series of tuitional strategies and Aprendizaje, in kind making use of means and educational concrete materials in order that students have the facility to develop and to increment their knowledge in the area in mention, in order that next the aforementioned knowledge, to take a resolution can put into practice multiple difficult situations in their everyday life._x000D_ In the development of the session, all facilities and corresponding support are offered, in order that students have complete confidence and autonomy in the acquisition of the new knowledge, in order that, to the to finalize the class, the students be in the capacity in order to apply for the learned, in the analysis of other proposed cases.